2001
DOI: 10.1108/14635780110383677
|View full text |Cite
|
Sign up to set email alerts
|

The initial return performance of UK property company IPOs

Abstract: This paper presents empirical evidence for a sample of 48 UK property company initial public offerings over the period 1986 to 1995. From which a number of conclusions can be drawn. First, property companies in general show positive average first day returns. Second, the average first day return by property trading companies is significantly higher than that for property investment companies 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…of 27%). Initial IPO returns are 6%, which is higher with regard to the underpricing levels found in REIT studies but in line with empirical results for property companies without a REIT regime (Sahi and Lee 2001;Brounen and Eichholtz 2002;Freybote et al 2008). Further, EPCs diluted their existing share capital by 44% and thereby raised, on average, EUR 125 mn.…”
Section: Descriptive Statistics and Correlationssupporting
confidence: 87%
“…of 27%). Initial IPO returns are 6%, which is higher with regard to the underpricing levels found in REIT studies but in line with empirical results for property companies without a REIT regime (Sahi and Lee 2001;Brounen and Eichholtz 2002;Freybote et al 2008). Further, EPCs diluted their existing share capital by 44% and thereby raised, on average, EUR 125 mn.…”
Section: Descriptive Statistics and Correlationssupporting
confidence: 87%
“…Portugal 10.5% (Almeida and Dugue, 2000); Turkey 14.16% (Durukan, 2002); Greece 9.07% (Tsangarakis, 2004), 52.7% (Kenourgios et al, 2007); the U.S. 18.64% (Jones and Ligon, 2009), and the UK 7.8% (Sahi and Lee, 2011). On the other hand, few earlier studies in India have shown first day returns 77.94% (Krishnamurti and Kumar, 2002) and this study report 22.22%.…”
Section: India-international Comparative Empirical Inferencescontrasting
confidence: 39%
“…Like previous studies, the chosen sample of Indian offers also reported negative returns in long-run (e.g. Ang and Boyer, 2009;Kumar, 2007;Sahi and Lee, 2011;Tsangarakis, 2004).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The other 22 were property trading companies that showed a 12.14% statistically significant first day return. Sahi and Lee (2001) however suggest caution in the interpretation of the latter result because 21 of the 22 property trading company IPOs listed during 1986 to 1989 which was a period in which the property market and property sector were booming. Chan, Stohs and Wang (2001) examined 56 property IPO companies and 343 non property IPO companies in Hong Kong over the period 1986 to 1997.…”
Section: The Underpricing Of Property Company Iposmentioning
confidence: 88%